Indonesian Student Research Olympiad for SMA N 1 Mirit Students - Prabowo, Agung; Chandra, Novita Eka; Juliza, Melda; Arumingtyas, Felinda (Shof Journal of Social Impact, 2024)
Olimpiade Penelitian Siswa Indonesia (OPSI) is a prestigious event that provides opportunities for students to develop research and innovation skills. This community service activity aims to guide and prepare students of SMA N 1 Mirit in facing OPSI. The benefits obtained by students after carrying out this activity are being able to master the material and being able to carry out research. The methods used in the guidance activities are the presentation of research methods, strategies, discussions and questions and answers. The results of the guidance activities are the level of student understanding in research methods of 75%, and the level of student interest of 80%.